The Daisy children - Grant, Sofia (William Morrow, an imprint of HarperCollinsPublishers, 2018)
When Katie Garrett gets the unexpected news that she's received an inheritance from the grandmother she hardly knew, it couldn't have come at a better time. She flees Boston - and her increasingly estranged husband - and travels to rural Texas. There, she's greeted by her distant cousin Scarlett. Friendly, flamboyant, eternally optimistic, Scarlett couldn't be more different from sensible Katie. And as they begin the task of sorting through their grandmother's possessions, they discover letters and photographs that uncover the hidden truths about their shared history, and the long-forgotten tragedy of the New London school explosion of 1937 that binds them.